Quality Of Waters Of Aquifer Webs Of Biskra Region - Bouchemal, F.; Bouchahm, N.; Achour, S. (University of Eloued جامعة الوادي, 2011)
Controlling the quality of water distributed together with sound resource management is a factor of economic and social development. Also, the chemistry and knowledge of geological and hydrogeological aquifer, the object of this work, we identify the water quality examined through physical-chemical parameters. The study of these parameters more precisely the region of Biskra reveals a generally high mineralized whose origin is essentially the geological nature of enclosing land. However, the waters of the continental interlayer (Albian) are the chemical profile weakest; however, its high temperature makes it difficult to use both to supply drinking water as well as for irrigation. After synthesis of the results for different sheets (groundwater, Miopliocene, Eocene, Albian), the limestone is most interesting at least for drinking water, part of its rate of mineralization (medium), the acceptable temperature (24°C) and its relatively low salinity (1 to 3 g/l). However, these waters are not used directly for human consumption. They requires further treatment.
Articale in Journal of fundamental and Applied Sciences Vol. 03 N. 01
Keywords: Aquifer, Biskra, mineralization, chemical profile, quality.